Chinese and Western Philosophical and Ethical Perspectives: Différance Rather Than Incommensurability or Sameness. (February 2017) - Sigurðsson, Geir
This experimental article claims that relatively recent trends in Western philosophy provide a much more open approach to philosophies originating in nonwestern traditions, including the Chinese, than found in most mainstream Western philosophy. More specifically, I argue that a slightly modified version of Jacques Derrida's concept of différance offers a hermeneutic parallel to native Chinese philosophical approaches to interpretation. These converge in the view that Western and Chinese philosophies cannot be reduced to the other in conceptual terms and that a finalized meaning or interpretation of each is a priori unattainable, thus providing a future opening for – and even integration of – a Chinese-Western dialogue in global philosophy and ethics. *